The Influence of Solution-Focused Therapy on Quarter-Life Crisis in Early Adult Women - Nabilah Fettiani; Yusmeileni; Alwi Siregar; Nurul Tri Anisa; Haryati Rahma (Journal of Psychology and Social Sciences, 2024)
Quarter-Life Crisis can defined as a period where someone feels uncertainty and confusion in their life. Early adult women are the group most frequently vulnerable to experiencing Quarter-Life Crisis because they often face pressures from social and personal responsibilities. Solution Focused Therapy is a therapeutic approach that focuses on finding solutions and is future-oriented. This study aims to fill the knowledge gap by investigating whether SFT therapy can reduce the symptoms of Quarter-Life Crisis in early adulthood women. This research uses a quasi-experimental one-group before and after study design. With two approaches, a quantitative approach using the Hassler questionnaire to measure the level of Quarter-Life Crisis and a qualitative approach using interviews and observations. Respondents consisted of 3 early adult women who experienced a quarter-life crisis. The results of the research prove that there is a difference before and after administering Solution Focused Therapy in the level of Quarter-Life Crisis of respondents, with a mean score in the pre-test of 120.67 and the post-test of 73.67. These results indicate that providing solution-focused therapy can significantly reduce the level of the quarter-life crisis.